Antibody-Mediated Graft Injury: Complement-Dependent and Complement-Independent Mechanisms - Valenzuela, Nicole M (2014)
PURPOSE OF REVIEW: Antibody-mediated rejection (AMR) is emerging as the leading cause of chronic rejection and allograft failure. Traditionally, the mechanisms of graft injury mediated by donor specific antibodies beyond complement activation were not well appreciated. However, an evolving paradigm of Fc-independent antibody functions, along with clinical recognition of C4d negative AMR, has increased awareness of the action of antibodies leading to endothelial activation and dysfunction. RECENT FINDINGS: Herein, we address current clinical trends, including the signature of microvascular inflammation in biopsies of grafts undergoing AMR, the prevalence of antibodies to HLA-DQ and non-HLA targets, and the functional characterization of HLA IgG subclasses and complement fixing capacity. We also discuss recent experimental evidence revealing new mechanisms of endothelial and smooth muscle cell activation by HLA antibodies, which may contribute to vascular inflammation and chronic rejection. Finally, we touch upon novel discoveries of the interplay between antibodies, the complement system and CD4 T cell-mediated alloimmunity. SUMMARY: The current literature suggests that, although complement fixing antibodies may have some prognostic value for graft outcome, complement-independent mechanisms of graft injury are increasingly relevant. Therapeutic strategies which target endothelial activation induced by antibodies may ameliorate vascular inflammation and mononuclear cell infiltration characteristic of AMR.